2016
DOI: 10.1016/j.actamat.2015.11.057
|View full text |Cite
|
Sign up to set email alerts
|

3D metallic glass cellular structures

Abstract: 3D Metallic glass structures (3DMGs) are fabricated through thermoplastic forming (TPF)-based patterning of MG sheets combined with a parallel joining technique. To demonstrate this capability and benchmark 3DMGs, we have fabricated honeycomb-like MG architectures covering a wide range of relative densities. 3DMGs exhibit high elasticity of up to 40% loading strain, high elastic energy storability, and high energy absorption which is superior compared to those made from other materials such as conventional met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…These authors observed that while the periodic structures generally had a higher elastic modulus and yield strength compared to stochastic structures, the stochastic onees exhibited higher flaw tolerance [35]. To create 3D periodically architected metallic glass structures, one study utilized thermoplastic forming-based patterning of metallic glass sheets combined with parallel joining, which resulted in honeycomblike architectures exhibiting high elastic energy storability and absorption [36]. 3D periodically architected metallic glass cellular structures were also fabricated using electroless deposition of Ni-P metallic glass onto a sacrificial polymer microlattice [37].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors observed that while the periodic structures generally had a higher elastic modulus and yield strength compared to stochastic structures, the stochastic onees exhibited higher flaw tolerance [35]. To create 3D periodically architected metallic glass structures, one study utilized thermoplastic forming-based patterning of metallic glass sheets combined with parallel joining, which resulted in honeycomblike architectures exhibiting high elastic energy storability and absorption [36]. 3D periodically architected metallic glass cellular structures were also fabricated using electroless deposition of Ni-P metallic glass onto a sacrificial polymer microlattice [37].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…These Ni-P microlattices consisted of ~1 mm unit cells with metallic glass wall thicknesses of 60 -600 nm and reported structures with wall thicknesses above 150 nm failed catastrophically while those with wall thicknesses below 150 nm failed with plasticity [37]. The dimensions of metallic glass lattices in nearly all of these existing studies were far from the nanoscale, including ~1 mm unit cells and 20-70 μm wall thicknesses [35], cm-sized unit cells and ~0.4 mm wall thickness [36]. and mmsized unit cells and ~60-600 nm wall thicknesses [37].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…The interface is expected to be intact, to form a high-strength bonding and to have other high-performance physical properties. Herein, due to the instantaneous process of HRS technique (much less than 1 ms) at room temperature, interface oxidation effect can be almost ruled out4041, which contributes to a well bonding condition at interface. It is advantageous comparing with the high temperature joining technique.…”
Section: Resultsmentioning
confidence: 99%
“…However, they demonstrated higher flaw tolerance, which also plays a significant role in achieving desirable properties in engineering materials. Based on the two-dimensional MG honeycombs, Liu et al have developed some 3D MG honeycomb structures using a parallel joining technique [67]. Theoretical analyses have shown that with a good combination of both high strength and elastic limit, these 3D MG honeycomb structures can demonstrate a high plastic energy absorption capacity, superior to those cellular structures made of conventional metals and ceramics.…”
Section: Mg Honeycombsmentioning
confidence: 99%